The effect of celery (Apium graveolens l) ethanol extract on the prevention of gastric ulcers in rats - Sartika Lestari Ismail, Dina Dewi; Kristianto, Heri; Sandra Novita Yunianto; Setyoadi, Setyoadi (University of Muhammadiyah Malang, 2024)
Background: Gastric ulcer is an excoriation area of the stomach caused by the destruction of mucosal defense against the predominant factors. One of the efforts that should be made to reduce the incidence of gastric ulcers is a precautionary measure to use ethanol extract of celery (Apium graveolens L). Celery contains phenolic compounds, such as apigenin which acts as an antioxidant. Antioxidant has the potential as an agent of gastric mucosal protection against cell damage caused by excessive activation of free radicals (ROS). Objectives: This study aimed to determine the effect of celery ethanol extract in preventing gastric ulcers through a reduction of ulcer lesion length. Method: Research method Post-test Only Randomized Controlled Group Design conducted on Wistar strain rats. Experimental animals were divided into 5 groups: healthy, normal wound with induction indomethacin, and celery ethanol extract administered orally at a dose of 200 mg/kg, 300, mg/kg, and 400 mg/kg. Observations were made on the length of gastric ulcer lesions. The length of the gastric ulcer was measured using a vernier caliper and statistically analyzed by the One-way ANOVA test. Result: The result showed that the ethanol extract of celery at 300mg/kgBB was the best dose in preventing the formation of gastric ulcer by decreasing the length of the gastric ulcer. Conclusion: Based on these results, the researcher suggests comparing other various parameters regarding the effect of celery ethanol extract for the prevention of gastric ulcers.